2018
DOI: 10.1080/15287394.2018.1488639
|View full text |Cite
|
Sign up to set email alerts
|

Single contaminant and combined exposures of polyethylene microplastics and fluoranthene: accumulation and oxidative stress response in the blue mussel,Mytilus edulis

Abstract: The microplastic "vector effect" has received increasing attention. The aim of this study was to investigate the influence of polyethylene microplastic beads (PE MP) on accumulation and associated oxidative stress responses attributed to fluoranthene (Flu) in blue mussels, Mytilus edulis. Blue mussels were exposed for 96 h to four treatment groups: Flu-only, MP-only, Flu and MP coexposure, and Flu-incubated MP. Treatments were conducted at a low and high concentration (50 μg/L and 100  Flu μg/L and 100, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…following a 7-day exposure to PS-MP, and Magara et al (2018) showed no effect on SOD activity in the gills or digestive glands of M. edulis exposed to 100-1000 PE-MP mL -1 for 4 days. Wang et al (2020) identified a non-significant increase in SOD activity in the digestive glands of the mussel Mytilus coruscus following 24 h exposure to microplastics, and no changes in SOD activity with longer exposure periods.…”
Section: Oxidative Balance: Sod and Tbarsmentioning
confidence: 81%
See 1 more Smart Citation
“…following a 7-day exposure to PS-MP, and Magara et al (2018) showed no effect on SOD activity in the gills or digestive glands of M. edulis exposed to 100-1000 PE-MP mL -1 for 4 days. Wang et al (2020) identified a non-significant increase in SOD activity in the digestive glands of the mussel Mytilus coruscus following 24 h exposure to microplastics, and no changes in SOD activity with longer exposure periods.…”
Section: Oxidative Balance: Sod and Tbarsmentioning
confidence: 81%
“…We posit that higher plastic concentrations may be sufficient to cause attrition within the gastro-intestinal tract resulting in the abrasion of tissues, leading to cellular damage and lipid peroxidation. It is recognised that oxidative stress responses can be variable, differing with genotype, age, reproductive status, feeding and temperature, and that a broader suite of biomarkers and wider literature should be considered in inferring biological pathways (Magara et al, 2018;Trestrail et al, 2020). Histological studies have shown that microplastics can permeate into the epithelial cells of the digestive gland resulting in epithelial thickening, the formation of granulocytomas and reduced epithelial cilia densities (Bråte et al, 2018;Paul-Pont et al, 2016;von Moos et al, 2012).…”
Section: Oxidative Balance: Sod and Tbarsmentioning
confidence: 99%
“…Further, bioaccumulation of chemical additives associated with MP uptake has also been documented, albeit in fewer species [54,57,71]. Interestingly, in all six species examined, uptake of chemical additives was higher when exposed to the chemical alone compared to exposure alongside or on MPs [57,59,60,67,71]. For most of the studies reporting bioaccumulation of MPs or chemical additives, the concentrations in the surrounding environment were not measured, hindering the elucidation of potential exposure pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4 species have been examined for contamination with chemical additive associated with MPs uptake under controlled laboratory exposures, namely the mussels Mytilus edulis [59] and Mytilus spp. [60], the clam Scrobicularia plana [61] and the amphipod Allorchestes compressa [57] (S7 Table in S1 File).…”
Section: Plos Onementioning
confidence: 99%
“…Bivalves are a group of animals that lack some of the common molluscan organs, such as the radula and odontophore, so they cannot chew when they eat. All their ingested food goes directly into the digestive system and can be used in MNPs research [80][81][82][83][84][85]. Most bivalves are filter feeders, including oysters, clams, shellfish, mussels, etc.…”
Section: Health Impacts Of Pristine Mnps Health Impacts Of Mnps On Mamentioning
confidence: 99%